Opportunity Amid Crisis in Medical Education: Teaching During the Pandemic of COVID-19 - Rahayu, Gandes Retno (Dove Medical Press, 2022)
Purpose: The pandemic of COVID-19 had reinforced adaptations in medical education. It was challenging, especially for developing countries where resources were scarce. This study examined the implementation of teaching and learning adaptation during the pandemic in a low-resource country as perceived by teachers. We also present the opportunities that arise from the adaptation process.